Lemons Markets and the Transmission of Aggregate Shocks - Kurlat, Pablo (American Economic Review, 2013)
I study a dynamic economy featuring adverse selection in asset markets. Borrowing constrained entrepreneurs sell past projects to finance new investment, but asymmetric information creates a lemons problem. I show that this friction is equivalent to a tax on financial transactions. The implicit tax rate responds to aggregate shocks, generating amplification in the response of investment and cyclical variation in liquidity. (JEL D82, D92, E32, E44, G31, L15)